Indirect Social Sanctions from Monetarily Unaffected Strangers in a Public Good Game - Mari Rege; Kjetil Telle (Statistics Norway, Research Department, 2003)
Several economists have maintained that social sanctions can enforce cooperation in public good situations. This experimental study investigates whether indirect social sanctions from monetarily unaffected observers can increase contributions to a public good. The experiment has two treatment effects. First, each participant's identity and contribution to the public good is revealed to the monetarily unaffected observers. Second, information affecting participants' beliefs about the degree to which the observers are contributors is introduced. The data suggests that indirect social sanctions from monetarily unaffected observers can increase voluntary contributions to public goods, provided that the subjects have reason to believe that the observers themselves are strong contributors.
Keywords: A13; C91; H41; Z13; 330; conditional; cooperation; public good; social approval; social norms